POLICY OF WORTHY CHILDREN REGENCY IN ANALYSIS FRAMEWORK OF THE VAN METTER AND VAN HORN POLICY IMPLEMENTATION MODEL - Fadlurrahman, Fadlurrahman (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2019)
Policy of worthy children regency (KLA) is the government effort in order to fulfill and protect children rights by involving stakeholders: government, private, non-governmental organization (LSM) and society. Magelang regency has received several awards related to KLA at the Pratama level (2012), and Madya (2015, 2016, 2017, 2018). This is a little contradictory to the fact that there are still problems related to children’s rights such as malnutrition, children without birth certificates, and child labor at age 10-18 years old. The purpose of this study is to analyze implementation of KLA in Magelang regency using the Van Metter and Van Horn model with qualitative method. Number of informants as many as 10 people. The result of study show there are obstacles in implementing KLA policy: lack of human and financial resources, weak communication between stakeholders, negative influence of thick social conditions, and lack of socialization. Recommendation to stakeholders inlcude: strengthening human and financial resources, increase the intensity of socialization and communication, and noting the social and economic conditiouns of community.